2021
DOI: 10.1590/1980-549720210015.supl.1
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of hypertension and diabetes mellitus prevalence according to Health Vulnerability Index in Belo Horizonte, MG, Brazil

Abstract: Objective: To estimate the prevalences of hypertension and diabetes for small areas in Belo Horizonte, according to the Health Vulnerability Index (HVI). Methods: Ecological study with data from the Surveillance of Risk and Protection Factors for Chronic Diseases by Telephone Survey (Vigitel) conducted in Belo Horizonte, from 2006 to 2013. The self-reported diagnosis of diabetes and hypertension were evaluated. The estimates of prevalence and the 95% confidence interval (95%CI) were calculated using the direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Globally, elevated systolic blood pressure is the single most significant risk factor for stroke (contributing 79.6 million disability-adjusted life years [DALYs] (7.7–90.8) or 55.5% (48.2–62.0) of the total DALY of stroke) [ 39 ]. Hypertension is a multifactorial chronic disease related to different outcomes, among which stroke is recognized as one of the main outcomes [ 40 ]. The Global Burden of Disease (GBD) estimates that stroke overload in older adults is expected to increase by 44% from 2004 to 2030 [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, elevated systolic blood pressure is the single most significant risk factor for stroke (contributing 79.6 million disability-adjusted life years [DALYs] (7.7–90.8) or 55.5% (48.2–62.0) of the total DALY of stroke) [ 39 ]. Hypertension is a multifactorial chronic disease related to different outcomes, among which stroke is recognized as one of the main outcomes [ 40 ]. The Global Burden of Disease (GBD) estimates that stroke overload in older adults is expected to increase by 44% from 2004 to 2030 [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no distinction between skin color and the chronic diseases analyzed in this research, NCDs more often affect lower-income populations because they have less access to health services and practices to promote health and prevent diseases. 19,20 The black population is more prevalently affected in different countries by basic diseases such as hypertension, diabetes, chronic kidney disease, cerebrovascular and cardiovascular diseases, which would result in a greater potential for the development of severe cases of COVID-19. 15 These findings are reinforced by other findings that showed that black people and communities with low purchasing power have worse outcomes of COVID-19 when compared to white people, the study conducted by the Center for Operations and Health Intelligence at PUC-Rio pointed out that of the total number of notifications for Covid-19 with outcome of deaths was 38% for the white population compared to 55% among black and brown people.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to CRVAs, health vulnerability indices are an emergent area of research, most notably in Brazil [ 21 , 22 ], with less research available in India [23] and the U.S [24] . On the African continent, these types of analysis are limited, but available, for example, in Sudan [25] and Ethiopia [26] .…”
Section: Introductionmentioning
confidence: 99%